Isopropyl 2,5-anhydro-3,4-di-O-tert-butyldiphenyl-silyl-L-ribonate - Glawar, A. F. G.; Watkin, D. J.; Sanjayan, G. J.; Tranter, G. E.; Edwards, Alison A.; Fleet, George W. J. (Acta Crystallographica Section E - Structure Reports Online, 2005)
Determination of the crystal structure of the title compound, C40H50O5Si2, firmly established its relative configuration and hence that of some related tetrahydrofuran carboxylates. The material crystallizes with Z' = 2. Except for the chiral centres, the two independent molecules are related by a pseudo-centre of symmetry.

Self-assembly with degenerate prototropy - Baruah, Pranjal K.; Gonnade, Rajesh G.; Phalgune, U. D.; Sanjayan, G. J. (Journal of Organic Chemistry, 2005)
This work describes a rational approach for addressing the prototropy-related problems in heterocycle-based self-assembling systems by the use of degenerate prototropy. As a proof of principle, the utility of degenerate prototropy is demonstrated herein by developing heterocycle-based AADD-type self-assembling modules that exist as ``single set of protameric pair (duplex)'' in both solution and solid states. These self-assembling modules are quickly accessible in good yield by reacting 2-amino-5,5-disubstituted-1H-pyrimidine-4,6-diones, available in one step by the condensation of (x,a-dialkyl malonates and free guanidine, with isocyanates. Evidence from NMR spectroscopy, ESI mass spectrometry, and single-crystal X-ray diffraction studies confirmed the formation of molecular duplexes. The effect of electronic repulsion in duplex formation is also investigated. Their ready synthetic accessibility, remarkably high propensity to crystal formation, and the novel property of degenerate prototropy would make these novel self-assembling molecules promising candidates for many proposed applications.

(Thio)urea-mediated benzoxazinone opening: mild approach towards synthesis of o-(substituted amido)benzamides - Nair, R. V.; Sanjayan, G. J. (RSC Advances, 2014)
C-terminal activation of N-acylated o-aminobenzoic acids and their derivatives during coupling reactions with amines would often pose a challenge due to the formation of a benzoxazinone intermediate, which may resist reacting with amines. This communication reports a mild approach towards the installation of an amide bond via benzoxazinone ring opening utilizing Schreiner's (thio)urea organocatalyst. Peptide coupling reactions oen encounter major hurdles because of the formation of side products during carbonyl activation of various amino acids, like N-carboxyanhydride, diketopiperazine etc. 1 1,3-benzoxazinones (Fig. 1) are a class of heterocyclic side products obtained upon C-terminal activation of anthranilic acid and their derivatives due to the intra-molecular cyclization of the benzamide oxygen, resulting in trace or no coupling. 2 Strategies meant either to avert its formation in situ or to react it with amines have been attempted through heating the reactants at elevated temperatures 3 and/or in the presence of bases. 2b,c However, such drastic conditions may cause quinazoline formation as well, owing to a second cyclodehydration of the coupled product. Moreover, applying such drastic conditions to amino acids may not be advisable due to the possibility of epimerization. We have been interested for quite some time in the devel-opment of foldamers containing the Ant–Pro reverse-turn motif (Ant ¼ anthranilic acid, Pro ¼ proline), Fig. 1. 4 The striking feature of this motif is its robust 9-membered-ring intra-molecular H-bonding network. Occasionally, the formation of a benzoxazinone intermediate causes a drastic fall in the yield of coupled products. 5 Owing to the reduced reactivity of benzox-azinones towards amine nucleophiles, we attempted different conditions, such as heating the reaction mixture and under microwave conditions. Unfortunately, these procedures led to only partial conversion of the oxazinone into the product. Aer extensive effort, we were successful in developing an efficient method for coupling a range of isolated benzoxazinone inter-mediates via nucleophilic ring-opening utilizing DBU (1,8-dia-zabicycloundec-7-ene) in DMF containing A molecular sieves. 5 However, in a few cases, this method produced only meagre yields of the coupled product. One such instance was the reac-tion of 2-(2-azidopropan-2-yl)-2H-benzo[d][1,3]oxazin-4-one 1a, Table 1 (isolated as the major by-product on activation of 2-(2-azido-2-methylpropanamido)benzoic acid) with H-L Pro-OBn to obtain compound 2a. Scanty yields of the product isolated under DBU-mediated opening conditions impelled us to explore a carbonyl activation route to open the azlactone moiety. Hence, we employed some lactone activating agents, such as Sc(OTf) 3 , Ti(O i Pr) 4 etc., but none of the trials were rewarding.